THE AUTONOMY OF FAMILY IN CARING ITS MEMBER WITH TB AT KAWANGU’S HEALTH CENTER, EAST SUMBA – AN ETHNOGRAPHY - YOSEPHINA ELIZABETH SUMARTINI GUNAWAN (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2015)
Introduction: Family’s involvement is getting bigger if one of its member needs continuous help due to their health problem. Family as the closest person has the important role in determining the success of TB’s treatment. This study aimed to know family’s autonomy in taking care of its member with TB. Methode: Qualitative method with ethnography approach was used. 15 participants. Data were collected by using an interview, FGD, field note, and observation. The result of interviewed has been analyzed with content analysis method. Result: the result showed 7 themes such as 1frame of reference, 2frame of experience, 3sources of support, 4kinds of support, 5stressor, 6coping mechanism, and 7stigma. The autonomy level of the family was in the lowest category. Conclusion: Family’s perception about TB described the lack of knowledge about the concept of TB, etiology, transmission, and prevention of TB in the family. The family supported their member but minimum sources belong to the family caused minimum support also. Having a member with TB and the length of TB’s treatment became a stressor to the family. The family used adaptive and maladaptive mechanism. Social label and stigma in the community made the patient and their family felt isolated and unconsciously causes the formation of isolating TB patient in the family.